How to make an artificial satellite out of a nuclear reactor. An exploration of research-technology emergence and management at INVAP*. (2nd October 2017) - Seijo, Gustavo
ABSTRACT: This paper analyses research-technology (RT) emergence and management at INVAP. INVAP is an Argentinean state-owned enterprise based in Bariloche, Patagonia. Most INVAP decision-makers find it challenging to develop technology to meet client-specific needs. RTs exploit interstitial boundary-crossing knowledge. Organisational technology-rooted R&D learning can be characterised as a joint, transverse, inter-departmental and inter-disciplinary process. RT-related technologies have the potential to be dis-embedded from a specific development-project and/or technological area and re-embedded in another project or area. This paper traces the historical dynamics of six RTs at INVAP. Its perspective marginalises the conventional R&D emphasis on the generation of new products and the improvement of production processes, and highlights the importance of monitoring RT emergence. It argues that technology-based product portfolio strategies can profit substantially from good RT management and planning.